Measuring and Analyzing the Relationship Between Global Warming and Economic Growth Using the Vector Autoregression (VAR) Model: Iraq as a Case Study for the Period (1990–2016) - Alaa Nouri Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Global warming driven by carbon dioxide emissions has become a central challenge to economic systems, particularly in developing and oil-dependent countries. Specific Background: Iraq, as a rentier economy heavily reliant on oil production, faces rising CO₂ emissions alongside fluctuating gross domestic product growth, especially during the period 1980–2016 marked by wars, sanctions, and structural instability. Knowledge Gap: Despite increasing environmental deterioration, limited econometric evidence exists on the dynamic relationship between global warming and economic growth in Iraq. Aims: This study analyzes the short-run and long-run interactions between CO₂ emissions and GDP using annual World Bank data and the Vector Autoregression model. Results: Unit root tests confirm stationarity at first difference, while the Engle–Granger test indicates no long-term cointegration between the variables. VAR estimates reveal weak but positive short-run interactions, where economic growth slightly increases emissions and past emissions strongly determine current emission levels, with model explanatory power reaching 96% and 89% respectively. Novelty: The study provides a structured econometric assessment of environmental and economic dynamics in Iraq using VAR modeling for the full 1980–2016 period. Implications: Findings highlight the short-term mutual dynamics between oil-driven growth and emissions, underscoring the need for diversification strategies and climate-focused economic policies in Iraq. Highlights:• No Long-Run Equilibrium Detected Between Co₂ Emissions and GDP.• Short-Term Dynamics Show Weak Reciprocal Interactions.• Past Emission Levels Strongly Determine Current Emission Trends. Keywords: Global Warming, Carbon Dioxide Emissions, Economic Growth, Vector Autoregression, Iraq